2007
DOI: 10.1016/j.acn.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) in patients with end-stage liver disease awaiting liver transplant

Abstract: Patients with ESLD uniformly performed below expectations on all RBANS index scores compared to the healthy normative sample (all p's<.0001) and they also displayed a "subcortical" pattern of cognitive performance (p<.0001). Performances on RBANS attention, language, immediate memory, and total index scores were correlated with education and ethnicity (r's range=|.32-.57|; p's<.01). There was no association between performance on any of the RBANS index scores or subtests and ESLD patient characteristics. In su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 51 publications
5
37
0
Order By: Relevance
“…However, group differences were only examined for the RBANS Total score and not the five Index scores. In a similar study, Mooney et al [11] found that patients with ESLD performed below expectation on the RBANS compared to the healthy standardization sample [9]. Consistent with Sorrell et al [10] they identified a subcortical pattern of impairment on the RBANS.…”
Section: Introductionsupporting
confidence: 66%
“…However, group differences were only examined for the RBANS Total score and not the five Index scores. In a similar study, Mooney et al [11] found that patients with ESLD performed below expectation on the RBANS compared to the healthy standardization sample [9]. Consistent with Sorrell et al [10] they identified a subcortical pattern of impairment on the RBANS.…”
Section: Introductionsupporting
confidence: 66%
“…While originally conceived of as a tool for the assessment of dementia in the elderly (Gontkovsky et al, 2004) its increasing popularity among clinicians has led to the examination of its clinical utility in diverse patient populations (Mooney et al, 2007). The RBANS has acceptable psychometric properties with respect to test -retest stability, internal consistency and concurrent validity (Gold, Iannone, & Buchanan, 1999;Hobart, Goldberg, Bartko, & Gold, 1999;Larson, Kirschner, Bode, Heinemann, & Goodman, 2005).…”
mentioning
confidence: 99%
“…Because one of the purposes of the pre-transplant evaluation is to rule out neurodegenerative diseases, such as Alzheimer's disease, it is important to include tests that can distinguish cortical from subcortical patterns of de fi cits. A couple of studies have found support for the utility of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) [ 116 ] in pre-transplant evaluations [ 117,118 ] , with one study con fi rming the expected subcortical pattern of de fi cits using the Randolph Cortical-Subcortical Deviation Score detailed in the RBANS manual [ 118 ] . When pre-transplant evaluations must be conducted on an inpatient basis and the patient can tolerate more detailed assessment (i.e., is at grade 2 HE or less), the RBANS may be a good choice since it taps multiple cognitive domains, can be administered in less than 30 min, and is easy to transport.…”
Section: Test Selectionmentioning
confidence: 99%
“…Ability to perform basic activities of daily living, such as bathing and dressing, are often not affected. Cognitive testing displays a frontal-subcortical pattern of de fi cits, with impairments most often seen in psychomotor speed, attention/concentration, visuospatial/constructional skills, and executive functions [66][67][68] . Poor performances on measures of learning and memory may be found but usually are secondary to attentional and visuospatial/perceptual dif fi culties rather than de fi cits in memory per se [ 69,70 ] .…”
Section: Clinical Presentationmentioning
confidence: 99%